Analisis Yuridis Praktik Diskriminasi Penjualan Tiket Umroh oleh Perusahaan Penerbangan Ditinjau dari Perspektif Hukum Perlindungan Konsumen - Khanifa Fauziah; Ariawan Gunadi (UNES Law Review, 2024)
The issue of consumer protection has in fact become a hot topic that needs attention from various parties, especially considering that every business activity involves consumers and there are consumer rights that must be fulfilled by entrepreneurs based on Law Number 8 of 1999 concerning Consumer Protection. Cases that have been widespread include discriminatory practices carried out by PT Garuda Indonesia (Persero) Tbk in selling Umrah tickets, closing access to ticket reservations by Garuda Indonesia to 301 PPIUs (Umrah Travel Organizers), so that consumers cannot reserve tickets directly. This problem then invites the author to discuss further regarding consumer protection in this case and the implementation of legal protection that should be for consumers in discriminatory practices in business activities. This research uses a normative juridical research method using literature study and a legal approach. The research results show that in constructing consumer protection, you must actually look at legal principles, both in terms of legal certainty, legal protection and justice, as well as referring to the principles of Islamic law. In implementing legal protection referring to the Consumer Protection Law, it is necessary to take several steps, including collaboration in supervising entrepreneurs by utilizing technology, clear and integrated regulations and the imposition of strict and proportional sanctions, as well as education for entrepreneurs to can always uphold consumer protection values including transparency, fairness, openness, equality.